Spontaneous disappearance of gallstones: presentation of two clinical cases - Zerboni, Eugenio R; Priario, Julio C (Cirugía del Uruguay, 2020)
Two cases of spontaneous disappearance of gall stones are reported. This is such an exceptional phenomenon that we are interested in let in know. W e don't have elements enough to know why gall stones have dísappeáred.